Identification of NY-ESO-1157–165 Specific Murine T Cell Receptors With Distinct Recognition Pattern for Tumor Immunotherapy - Zhang, Helin; Sun, Meng; Wang, Jie; Zeng, Bin; Cao, Xiaoqing; Han, Yi; Tan, Shuguang; Gao, George F. (Frontiers in Immunology, 2021)
NY-ESO-1 is a promising target for T cell receptor engineered T cell (TCR-T) therapy, and targeting the HLA-A2 restricted NY-ESO-1157-165 epitope has shown remarkable clinical benefits in the treatment of multiple advanced malignancies. Here, we report the identification of two NY-ESO-1157-165 epitope specific murine TCRs from HLA-A*0201 transgenic mice. NY-ESO-1 specific TCRs were isolated through vaccination of epitope peptide in HLA-A2 transgenic mice. HZ6 and HZ8 TCR could specifically bind to NY-ESO-1157-165/HLA-A2 and were capable of IL-2 and IFN-γ secretion with engineered Jurkat T cells and/or primary T cells upon recognition with K562 target cells expressing single chain trimer (SCT) of NY-ESO-1157-165/HLA-A2. The reactivity profiles of HZ6 and HZ8 TCRs were found to be distinct from each other when co-cultured with K562 target cells carrying alanine substituted NY-ESO-1157-165 SCTs, which were in consistent with the binding affinities tested by SPR analysis. A comparative analysis revealed that the recognition pattern of HZ6 TCR to NY-ESO-1157-165/HLA-A2 was substantially different from the widely applied 1G4 TCR. These findings would broaden our understanding of the immunogenicity of NY-ESO-1157-165, and the two identified TCRs may serve as promising candidates for future development of TCR-T cell therapy for tumors.